2004
DOI: 10.1055/s-2004-827042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin on the severity of L-arginine-induced experimental acute pancreatitis in rats

Abstract: tonin given in advance of L-Arg significantly reduced the pancreatic CAT activity relative to that in the rats treated with L-Arg alone. In the liver, L-Arg significantly increased the lipid peroxidation level, and the glutathione peroxidase and Cu/Zn-SOD activities, whereas the Mn-SOD activity was reduced as compared to the control rats. Melatonin pre-treatment prevented these changes. CONCLUSION:Melatonin is an antioxidant that is able to counteract some of the L-Arg-induced changes during acute pancreatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…This model is ideal due to its non-invasive and non-invasive nature and the fact that it causes dose-dependent acinar cell necrosis, allowing studies on the pathogenesis of acute pancreatitis. Szaboles et al 12 have also used L-arginine to develop pancreatitis from which they have earned good results.…”
Section: Introductionmentioning
confidence: 99%
“…This model is ideal due to its non-invasive and non-invasive nature and the fact that it causes dose-dependent acinar cell necrosis, allowing studies on the pathogenesis of acute pancreatitis. Szaboles et al 12 have also used L-arginine to develop pancreatitis from which they have earned good results.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin exerts its beneficial effects through several mechanisms, including scavenging free radicals, activating antioxidative enzymes, inhibiting neutrophil infiltration, promoting neutrophil apoptosis, modulating cytokine production and altering the generation of pancreatic prostaglandins [10,11,18,22,30,46,50]. In addition, the melatonin precursor, L-tryptophan, increases the level of melatonin in the blood and attenuates AP in rats [22,26,50].…”
Section: Discussionmentioning
confidence: 99%
“…The change in levels of catalase and SOD remains controversial. Czako and Takacs 25 reported the fall in these enzyme levels at 24 h. However, Szabolcs 24 reported the raised levels of these enzymes. In consistent with Robbins, 2 in the present study significant increase in SOD and catalase level was observed.…”
Section: Assessment Of Interleukins and C-reactive Proteinmentioning
confidence: 95%
“…In consistent with previous reports alpha-pinene has significantly reduced the raised level of acinar cell necrosis, serum amylase and lipase. 5,18,19 One of the important diagnostic markers for acute pancreatitis are serum amylase and lipase, which rise within four to eight hours of initial attack and will be peak at 24 hours. Treatment with alpha-pinene decreased the serum amylase and lipase levels, indicating protective effect of alpha-pinene at early stage of the disease progression.…”
Section: Assessment Of Interleukins and C-reactive Proteinmentioning
confidence: 99%
See 1 more Smart Citation